PROFIL KLINIS DAN LUARAN STROKE ISKEMIK AKUT DENGAN TROMBEKTOMI MEKANIK BERDASARKAN LOKASI OKLUSI DI RSUPN DR. CIPTO MANGUNKUSUMO - Kevin Kevin; Taufik Mesiano; Mohammad Kurniawan; Rakhmad Hidayat; Affan P. Permana; Al Rasyid; Salim Harris (PERDOSNI, 2021)
Introduction: Occlusion in anterior circulation gives variable clinical manifestations. Mechanical thrombectomy promises almost two times higher recanalization rate as opposed to thrombolysis. Aim: To evaluate the clinical and outcome profile of acute ischemic stroke patients who underwent mechanical thrombectomy based on the occlusion site. Methods: This was a retrospective cohort conducted at Cipto Mangunkusumo National Referral Hospital from May 2017 to January 2020. All acute ischemic stroke patients in anterior circulation who underwent mechanical thrombectomy with or without bridging intravenous thrombolysis were analyzed. Occlusion site and recanalization rate were scored based on arteriogram. Results: Sixteen patients had occlusion in ICA-M1 segment, while ten others were in the M2 segment. NIHSS value was two points higher in ICA-M1 occlusion (p>0.05), which further analysis found that the proportion of aphasia manifestation was higher in the ICA-M1 segment (50.0% vs 20.0%; p=0.218). Demographical and clinical characteristics were similar between the two groups. Thrombolysis did not modify the occlusion site on thrombectomy (p>0.05). Despite statistical insignificancy, ICA-M1 occlusion showed an earlier time trend from admission to recanalization. The M2 segment had a higher proportion of mTICI 2b/3 recanali????ation (50.0% vs 70.0%; p=0.428) and mRS 0-2 on discharge (12.5% vs 50.0%; p=0.053). Discussion: Aphasia was more common in proximal occlusion???? which drove family members to bring patients earlier to the hospital. The functional outcome on discharge was lower in proximal occlusion due to more extensive and permanent brain tissue loss. Future coordination is warranted to improve the therapeutic time from admission to recanalization. Keywords: functional outcome, ischemic stroke, mechanical thrombectomy, occlusion site